2d pentagonal Pd-based Janus transition metal dichalcogenides for photocatalytic water splitting - You, Liming (2022)
Janus transition metal dichalcogenides (TMDs), which differ from their conventional counterparts by exhibiting two different layers of chalcogenides and an asymmetric out-of-plane structural configuration, are theorized to exhibit a relatively wide variety of properties. Herein, the structural, electronic, and optical properties of three Janus Pd-based TMD monolayers (PdSSe, PdSTe, and PdSeTe) are investigated through comprehensive density functional theory calculations. The most stable ground-state configurations of these Janus TMD monolayers correspond to the unique pentagonal configuration instead of the common 1T or 2H phases. The monolayers are semiconductors with moderate bandgaps (2.06–2.21 eV) and anisotropic optical absorption properties. By exhibiting suitable band edge positions with respect to the redox potentials of water, they can simultaneously facilitate the hydrogen and oxygen evolution reactions as water-splitting photocatalysts. In addition, the effects of uniaxial and biaxial strains on the optoelectronic properties of the monolayers are investigated, and it is determined that the application of strain reduces their bandgaps and causes a redshift of their optical absorption spectra, thereby allowing them to harvest ultraviolet and visible photons more effectively. An insight on the intrinsic properties of 2D Pd-based Janus TMDs is provided, which elucidates the rational design of photocatalysts for water splitting.